Pengaruh Pelatihan dan Disiplin Kerja Terhadap Kinerja Organisasi Dengan Kompetensi Sebagai Variabel Intervening Rumah Makan Boga Raso - Tirani Hikmah Nur Ulfah; Nurul Hermina (Intitut Agama Islam Nasional Laa Roiba Bogor, 2026)
This study aims to analyze the effect of training and work discipline on organizational performance with competence as a mediating variable at Boga Raso Restaurant. This research employed a quantitative approach using a survey method. Data were collected through questionnaires distributed to employees of Boga Raso Restaurant. The data analysis technique used in this study was Structural Equation Modeling–Partial Least Square (SEM-PLS) to examine the relationships among research variables. The results of the study indicate that training and work discipline have a positive and significant effect on employee competence. Furthermore, competence has a positive and significant effect on organizational performance. In addition to the indirect effects, training and work discipline are also proven to have a positive and significant direct effect on organizational performance. The results of the indirect effect analysis show that competence is able to mediate the relationship between training and organizational performance as well as between work discipline and organizational performance. These findings suggest that improving the effectiveness of training programs and consistently implementing work discipline can enhance employee competence, which ultimately contributes to improved organizational performance. Therefore, Boga Raso Restaurant is encouraged to continuously develop structured training programs and strengthen work discipline as a strategy to achieve sustainable organizational performance improvement.